Regularity and Uniformity in the Ethiopian Hagiographical Tradition: A Particular Focus on Narrating the Childhood of Saints - Alehegne, Mersha (Aethiopica, 2015)
The paper is an attempt to show how uniformity and regularity characterize the childhood of different Ethiopian saints as it is sketched in the Ethiopic hagiographic tradition. Presenting ample evidences from different hagiographies of Ethiopian saints, it tries to show how the saints’ early life follows a set of standardized patterns which are seen nearly as universal convention that is almost interchangeable between one saint and another. The discussion is focused on three patterns (infertility, prophecy/vision and old-child) of childhood where uniformity and regularity in the tradition are evident.